บทบัญญัติรัฐธรรมนูญว่าด้วยสถานะของสถาบันพระมหากษัตริย์ - วิชชุ วุฒานุรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This thesis focuses on the status of the King by considering written Constitutions of some countries having constitutional monarchy system, including each country’s historical background and political context, as well as, development of the Constitution regarding the status of the King in each country, in order to do a comparative study on the status of the King between these countries and the Kingdom of Thailand, which is a country ruled by the constitutional monarchy with the written Constitution. From this study, it was found that the status of the King in the countries having constitutional monarchy system usually follows the rules which are written in the Constitutions, along the same line of the willing of people, as well as, the socio-political context of these countries, whether such Constitutions came from people. However, when the status of the King in the Constitution is not in accordance with the common willing of the people or the socio-political context of the countries, it is unavoidable to change or amend the Constitutions. In case of Thailand, the King has long been supporter and welfare provider to the Thai people and has been acted as main player participating in the development of quality of life of the people since the period before the country’s political revolution in B.E. 2475 (A.D. 1932). After such revolution, pattern of writing various provisions, including those on the status of the King, in the Constitutions has been followed that of foreign countries, which concentrated more on limiting role and power of the King, and paid less attention on maintaining the socio-political context of the country. When the law in book and the law in action did not go together, the status of the King under the Constitution must be changed, particularly during the enactment of the new constitution in B.E. 2492 (A.D. 1949). In addition, the study elaborates that the King of the Kingdom of Thailand also has other statuses which derived from tradition and historically inherited from the social power of the King according to the socio-political context of the Kingdom of Thailand. No matter how many times the Thai Constitutions has been repealed, this type of power makes the status of the King of the Kingdom of Thailand always be remained as long as the Thai people have respected and been faithful to the King as it always has been.